Suppression of methanogenesis in paddy soil increases dimethylarsenate accumulation and the incidence of straighthead disease in rice. (June 2022) - Chen, Chuan; Yang, Baoyun; Gao, Axiang; Li, Lingyan; Dong, Xiuzhu; Zhao, Fang-Jie
Abstract: Some soil microbes can methylate arsenic (As) and produce dimethylarsenate (DMA) as a main product. Excessive accumulation of DMA by rice plants can cause the straighthead disease, a physiological disorder leading to substantial yield losses. DMA can also be demethylated in soil, but the mechanism and the microbes involved are not well understood. We investigated the dynamics of methylated As species, including monomethylarsenate (MMA), DMA and dimethyl-monothioarsenate (DMMTA), in three paddy soils that produced the straighthead disease. The soils were incubated under flooded conditions with or without the addition of 2-bromoethanesulfonate (BES), a specific inhibitor of methanogenesis. DMA and DMMTA concentrations in porewater increased initially as soil redox potential decreased, and then decreased rapidly coinciding with the production of methane. BES addition largely suppressed methanogenesis and the disappearance of DMA and DMMTA, but not of MMA. BES addition suppressed the transcript levels of archaeal 16S rRNA and, particularly, mcrA gene encoding methyl-coenzyme reductase subunit A. Among the core genera of archaea, the absolute abundances of Methanomassiliicoccus and Methanosarcina were decreased significantly by BES in the three soils. In a pot experiment with two soils, BES addition significantly increased DMA accumulation in rice husks and the incidence of the straighthead disease in rice. The results suggest that DMA and DMMTA demethylation in paddy soil is coupled to methanogenesis with Methanomassiliicoccus and Methanosarcina likely playing an important role. Highlights: High potential of arsenic methylation in paddy soils producing rice straighthead disease. Dimethylarsenate demethylation was coupled to methanogenesis in flooded paddy soils. Suppression of methanogenesis increased rice DMA accumulation and straighthead disease. Methanomassiliicoccus and Methanosarcina were likely involved in DMA demethylation.